(untitled) (Publicatio UEPG: Ciências Sociais Aplicadas, 2025)
Restorative justice has emerged as a potential way of rethinking accountability in criminal conflicts, but its adaptation to Brazil must take into account the preponderance of racism in social relations. The present study, through qualitative research, employing bibliographical and documental investigation, and adopting the hermeneutic-critical method, aims to analyze the remnants of racism in the Brazilian mindset, and the importance of humanizing black people in order to enable the responsibility sought by restorative justice. Initially, it discusses stigmatization/labelling, dehumanization and deindividuation and their effects on black bodies. It also addresses the adaptation of Brazilian racism to positivist discourses. Next, we proposed an approach to the symbolic dimension of the restorative encounter, based on the ethics of alterity and the ethics of non-violence. Finally, we attempted to concretely investigate how to make anti-racist restorative justice possible, and concluded that it is essential to raise awareness and train mediators to deal with cases of imbalance related to race.